Analysis of the Pedagogical Competency of Economics Teachers on the Learning Achievement of Eleventh-Grade Students at Muhammadiyah High School Maumere - Hendra, Mas; Abd. Rahman, Nurdin H.; Fitri, Mohammad (Contemporary Education and Community Engagement (CECE), 2024)
The research aims to determine the pedagogical competence of economics teachers at SMA Muhammadiyah Maumere and to ascertain the impact of the pedagogical skills of economics teachers on the academic performance of eleventh-grade students. The research method employed is a qualitative approach, utilizing a case study methodology. The research subjects were economics teachers and high school eleventh-grade students. This research has primary and secondary data. Primary data in this research is from the results of interviews and student grades, while secondary data is from sources such as journals and other documents from volunteers involved in this research. The author collected data using observation, interview, and documentation techniques. Meanwhile, to analyze the data the author uses data reduction, organizing and processing data, interpreting data, and verifying and drawing conclusions. The findings of this research explain that the pedagogical competence of teachers at Muhammadiyah Maumere High School has mastered student character and everything related to learning tools, so the average student score has reached above the minimum criteria. Meanwhile, learning achievement is a change in behavior covering three aspects (cognitive, affective, and motoric) such as mastery, use, and assessment of various knowledge and skills as a result or result of the learning process with factors that influence it are stated in the form of grades given by teachers and teacher competency has a positive effect on student learning achievement, so the higher the teacher's competency, the higher the student learning achievement. Student learning outcomes have a positive influence because students can achieve the desired results. Teacher competency has a positive effect on students' learning outcomes through the student learning process, so it can be concluded that the higher the teacher's personality competency through the student learning process, the higher the student learning achievement.